Prospective Randomized Observational Pilot Trial Evaluating the Effect of Information of Early Childhood Intervention on Stress Levels of Parents of Extremely Low Gestational Age Infants at the NICU - Resch, Bernhard; Fröhlich, Judith; Murg, Katharina; Pichler-Stachl, Elisabeth; Hofbauer-Krug, Claudia; Kurz, Ronald (Frontiers in Public Health, 2021)
It is not known to what extend early information on early childhood intervention (ECI) by ECI professionals reduces or increases stress levels of parents having an extremely preterm infant at the neonatal intensive care unit (NICU). By means of an observational pilot study we gave information on ECI in a randomized matter to parents of an extremely low gestational age newborn (ELGAN) at the chronological age of 3-4 weeks (cases) or not (controls). After informed consent parents judged the infants at the age of 6 weeks (± 1 week) with the Parental Stressor Scales: Neonatal Intensive Care Units [PSS:NICU has 3 subscales = “Sights and Sounds” (5 items), “Parental Role Alteration” (14 items), and “Look and Behave” (7 items)]. We aimed to measure parental stress levels having an ELGAN hospitalized at the NICU following standardized information on ECI. Total score and subscale scores did not differ between groups (13 cases and 13 controls). Total scores were 9.32 ± 0.72 in the cases compared to 10.02 ± 0.76 in the control, (CI95% -6.933 – 4.933). Early information on ECI at the NICU provided to parents with an ELGAN did not result in higher stress levels measured with the PSS:NICU. Whether early information on ECI might be able to reduce parental stress levels has to be proven in larger studies.